Serological Cross-Reactivity Between Bovine alphaherpesvirus 2 and Bovine alphaherpesvirus 1 in a gB-ELISA: A Case Report in Italy - Petrini, Stefano; König, Patricia; Righi, Cecilia; Iscaro, Carmen; Pierini, Ilaria; Casciari, Cristina; Pellegrini, Claudia; Gobbi, Paola; Giammarioli, Monica; De Mia, Gian Mario (Frontiers in Veterinary Science, 2020)
In this study, we demonstrated for the first time in Italy, the serological cross-reactivity between Bovine alphaherpesvirus 2 (BoHV-2) and Bovine alphaherpesvirus 1 (BoHV-1). Five months after arriving at a performance test station in Central Italy, a 6-month-old calf, which was part of a group of 57 animals, tested positive for BoHV-1 in a commercial gB-ELISA test. It was immediately transferred to the quarantine unit and subjected to clinical observation and serological and virological investigations. During this period, the calf showed no clinical signs. The results from laboratory investigations demonstrated the presence of antibodies via competitive glycoprotein B (gB) ELISAs, indirect BoHV-1 ELISAs, and indirect BoHV-2 ELISAs. Furthermore, the plaque reduction assay provided evidence for the presence of antibodies only for BoHV-2, whereas the virus neutralization test showed negative results for both BoHV-1 and BoHV-5. These findings strongly suggest the occurrence of a serological cross-reactivity between BoHV-2 and BoHV-1. Interference of BoHV-2 antibodies in serological BoHV-1 diagnostics should be considered during routine IBR tests, especially when animals are kept in a performance test station.